The effect of different treatments on its seeds and additional feeding in addition to the root in increasing the yield of spring wheat in the Aralsea region - Atamuratov R.T; Dauletmuratov М.М; Orazmetova R.S (Zien Journals, 2024)
In the article, in the Republic of Karakalpakstan, especially in the Aral Bay region, in weak and medium salinity areas, resistant to drought and diseases, spring soft wheat seeds with high yield and grain quality are treated before planting, as well as by root or leaf feeding, on the initial biometric indicators of wheat, the development of the root system and productivity. the results of the research carried out within the study of the effect of macro and micro fertilizers are presented
Keywords: Spring soft wheat; drained meadow alluvial soils; salinity level